Factors Associated with the Risk of Acute Respiratory Tract Infection (ARI) Symptoms in Toddlers Reviewed from the Home Environment in Bababan Village, Tulungagung Regency - Nurwijayanti; Vanessa Axelia Putri Sandya; Panca Radono (Journal Of Nursing Practice, 2025)
Background: Acute Respiratory Tract Infection (ARI) is a common illness caused by viral or bacterial infections, often perceived as non-threatening. ARI symptoms range from mild to severe and depend on pathogens, environmental factors, and host immunity. Purpose: This study aimed to identify factors associated with ARI symptoms in toddlers, focusing on home environmental conditions in Babadan Village, Tulungagung Regency. Methods: The study was conducted in 2023–2024 using a cross-sectional design with 60 respondents. Participants were mothers of toddlers showing ARI symptoms, living in Babadan, and willing to participate. Data were collected using questionnaires and observation sheets assessing home ventilation, air pollution, smoking behaviors, and ARI symptoms. Statistical analysis with Chi-Square was used to evaluate the relationship between environmental factors and ARI symptoms. Results: The findings indicated significant relationships between ARI symptoms in toddlers and home ventilation (p = 0.004), indoor air pollution (p = 0.012), and family members' smoking behavior (p = 0.017). Among these factors, smoking behavior posed the highest risk for ARI symptoms in toddlers. Conclusion: The study concludes that poor home ventilation, indoor air pollution, and smoking significantly contribute to ARI symptoms in toddlers, with smoking behavior being the most critical risk factor. Addressing these environmental issues could reduce ARI risks in children.